Regulating the Elderly: Old Age Pensions and the Formation of a Pension Bureaucracy in Ontario, 1929-1945 - Struthers, James (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 1992)
AbstractThis article examines the emergence of means-tested old age pensions in Ontario in the context of the Great Depression and World War II. Ontario's old age pension scheme, it argues, was launched in 1929 with weak political commitment, little bureaucratic-preparation, and an almost complete absence of administrative experience at the provincial and municipal level in assessing and responding to need on a mass scale. The article examines the complex interplay among federal, provincial, and local government authorities in the politics of pension administration throughout the 1929-1945 era, arguing that local control of pension decision-making in the early years of the Depression provided two divergent models of pension entitlement both as charity and as an earned social right. After 1933 governments at both the provincial and federal level centralized decision-making over pension administration in order to standardize and restrict pension entitlement, contain its rapidly rising costs, and enforce more efficiently the concept of parental maintenance upon children. World War II undermined the concept of pensions as charity by broadly expanding the boundaries of entitlement both for the elderly and their children. By 1945 means-tested pensions had few supporters within or outside of government, laying the basis for the emergence of a universal system of old age security in 1951.